PENGARUH LINGKUNGAN KERJA FISIK DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT POS INDONESIA (PERSERO) KANTOR CABANG CIPUTAT TANGERANG SELATAN - Tatu Alifya; Uswatun Chasanah (Journal of Research and Publication Innovation, 2025)
The aim of this research is to find out the impact of the physical work environment and work discipline partially or simultaneously on the performance of employees at the PT Pos Indonesia (persero) office of the branch of ciputat tangerang south. The method used in this research is the quantitative descriptive method, the sample used is the simple random sampling technique. The population and sample in this study was a population of 140 employees and a sample of 58 respondents. Research results show that there is a partial influence on the physical working environment and employee performance. Where the simple linear regression equation Y = 18,819 + 0,426 X1, the correlation test r = 0,614, included in a strong catagore, the determination coefficient of 33,7%, the t-test of t counts greater than the table or 5,821 > 1,672 H0 was rejected and Ha accepted. The results of the study that there is an influence between work discipline and employee performance in a partial way. Where a simple lineary regression Equation Y= 14,568 + 0,637 X2, the correlation test R = 0,692, included in the strong catalogue, a determination factor of 47,9%, a t-tone test larger than the t table 7,172 > 1.672 or H0 were rebut and Ha received. The result of the research that there was an effect between the variable of the physical work environment and the working discipline on the employee simultaneously. Where the ratio of the double regression Y= 9,967 + 0,239 + 0,461 X92, the core test of X was heard with the value of 0,751 of the work line, the test could include more than 544%, the physical performance of employee can be determined with the size of a variable work environment.